Endovascular treatment of aortic coarctation using covered balloon-expandable stents—a systematic review and meta-analysis - He, Fei; Cao, Zhongze; Wang, Chen; Premaratne, Shyamal; Starnes, Benjamin W.; Shu, Chang; Zhang, Wayne W. (Frontiers in Cardiovascular Medicine, 2024)
Objectives Balloon dilation followed by balloon-expandable stent implantation is an effective treatment for improving hemodynamic status in patients with coarctation of the aorta (CoA). However, limited evidence exists regarding the safety and efficacy of covered balloon-expandable stents (CBSs) in a large cohort. In this meta-analysis, we aimed to evaluate the overall success rates, hemodynamic and anatomical benefits, complications, and mid-term results of CBSs in treating CoA. Methods The PubMed, Embase, and Cochrane Library databases were systemically searched for studies reporting outcomes of CBSs in treating CoA. Single-group rate meta-analyses were performed to calculate estimated pooled procedural success rates, the incidence of complications, and re-coarctation rates. A meta-analysis using standardized mean differences was conducted to compare pre- and postoperative trans-coarctation pressure gradients (PGs), coarctation diameter, and overall changes in systolic blood pressure (SBP). Subgroup analyses were performed to identify potential sources of heterogeneity. Results The final analysis included 12 studies with a total of 411 patients. The estimated pooled procedural success rate was 100% [95% confidence interval (CI): 98%–100%, I2 = 0, P = 0.78]. Significant decreases in trans-coarctation PGs and SBP were observed. The pooled incidences of stent-related, aortic, and access site complications were 2% (95% CI: 0%–5%, I2 = 30.4%, P = 0.15), 2% (95% CI: 0%–4%, I2 = 0%, P = 0.76), and 3% (95% CI: 1%–7%, I2 = 52.9%, P = 0.02), respectively. Subgroup analyses showed that implantation of BeGraft stents was related to a significantly higher incidence of access site complications. Conclusion Covered balloon-expandable stent implantation in treating CoA is safe and effective with high procedural success rates, an acceptable incidence of complications, and a low incidence of re-coarctation. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/, PROSPERO (CRD42023430356).